Multi-speed Europe? An Analysis of the Real Convergence within the European Union - Miron , Dumitru; Holobiuc, Ana-Maria (KnE Social Sciences, 2020)
Reaching an appropriate level of economic, social and territorial convergence has been a strategic goal for European policy and decision-makers. The author’s first assumption is that although in the early stages of the regional project, the Member States had similar growth and development levels, with the advancement of the integration process, the development asymmetries increased. In this paper, the authors stress the fact that the European decision-makers and researchers have become more and more interested to study if the Member States of the European Union meet the criteria for certain types of convergence: nominal, real, legal, structural and institutional. This paper brings to the fore-front the process of real convergence, trying to respond to the question if the Member States are catching-up, or are diverging. Moreover, taking into consideration the enlargement of the European Union with the countries from Central and Eastern Europe, we have studied the main trends within this group of countries. In this respect, we have calculated the σ and β convergence for three geographical clusters of countries: Central Eastern, North Western and Southern Europe. The results obtained show that the economies of the New Member States increased faster than those of the North-Western countries, experiencing a significant speed of convergence. In contrast, the North-Western countries recorded a negative pace in terms of convergence and significant discrepancies between them. In conclusion, the paper shows that the desiderate of real convergence becomes more and more difficult to achieve as while the Central and Eastern Europe states make important steps in reducing the disparities between them and also catching up with the European Union’s average, the Southern Europe countries are diverging. Keywords: European Union, real convergence, σ-convergence, β-convergence